Analisis Tingkat Stres Akademik Mahasiswa Menggunakan Metode Proporsi Dan Confidence Interval - Denisha Lintang Viviani; Jihan Fahira; Siti Lusinta; Sipa Apiyanti; Perani Rosyani (Shofanah Media Berkah, 2025)
Academic stress is a common problem experienced by university students and may have negative impacts on mental health and academic performance. This study aims to analyze the proportion of students experiencing high levels of academic stress and to estimate the confidence interval (CI) of that proportion. The method employed is descriptive statistical analysis using a proportion confidence interval approach based on data obtained from a student stress questionnaire. The data were analyzed by calculating stress level proportions and presented in the form of proportion tables and bar chart visualizations to illustrate the distribution of students’ stress levels. The results indicate that a proportion of students experience high academic stress within a certain confidence interval range, reflecting the uncertainty of proportion estimation in the student population. These findings suggest that high academic stress remains a significant condition among students and requires attention. Therefore, this study is expected to provide an initial overview of students’ stress conditions and serve as a consideration for higher education institutions in designing stress prevention and management programs to improve student well-being.